Discurso, gênero e violência : uma análise de representações públicas do crime de estupro - Figueiredo, Débora de Carvalho (2017)
From a critical perspective, we can say that discourse shapes and defines social life (Fairclough, 1992), that is, discourse not only reflects and represents society, it also helps to signify, build and modify what we understand as ‘reality’. One of the effects of the constitutive nature of discourse can be seen in the creation  and transformation of social identities. Based on the theoretical frameworks of critical discourse analysis and gender studies, in this article I discuss how two dominant public discourses (media discourse and legal discourse) represent and construct rape – a social event structured around/by rigid and unequal relations of power and gender – and its main participants, the rapist and the victim. I also discuss the impact of these discursive representations on the police and on the legal treatment given to perpetrators and victims of rape, as well as on the way women conceive crimes of sexual violence, sexuality and their own identities.